PRE-PROCESSING EFFICIENCY RAW MATERIALS TO INCREASE PECTIN'S OUTPUT - G. V. Alekseev; O. A. Egorova; A. G. Leu (Современная наука и инновации)
The article discusses a more environmentally friendly method of pectin production compared to the classic acid scheme, which requires the use of strong mineral acids and toxic solvents.